Development of the method for estimating serviceability of equipment for the transportation of compressed natural gas - Dzhus, Andriy; Andrusyak, Andriy; Grydzhuk, Jaroslav; Romanyshyn, Taras (Eastern-European Journal of Enterprise Technologies, 2018)
To ensure safe transportation of compressed natural gas, we proposed, based on the results of studies conducted, the algorithm for a method for the evaluation of combined type tanks. The method implies determining parameters of the state of gas in the process of filling a tank, taking into consideration heat exchange processes and evaluation of the stressed-strained state of the tank, considering the operating conditions and the results of technical inspection. To implement the method, the tools for detecting and determining the shape and dimensions of probable corrosive damages of the metal liner surface under the composite shell were used. It was proposed to assess the stressed-strained state of tanks, taking into consideration the operating conditions, through the development and analysis of relevant models. The possibility of obtaining reliable results in the presence of available mechanisms was proved by our own research into the patterns of loading and unloading processes. To verify correctness of construction of the simulation model at the stage of studying the stressed-strained state of the tank with consideration of the actual operating conditions, we proposed the mathematical model that takes into consideration conditions for the interaction between elements of the structure, the effect of internal gas pressure and temperature. The use of the model decreases the costs of experimental research and contributes to ensuring the reliability of simulation results. The advantage of this method is determining the estimated destruction pressure of the combined type tanks at the current state of the dangerous areas and the influence of operating conditions. The practical significance of the obtained results is determined by the possibility of their application to ensure serviceability at the design stage and when tanks are in operation.